ASR, Volume 16, n° 2, 2012 - Full Issue - Journal System, (African Sociological Review, 2013)
Contents Editorial .................................1 General Issues Community Sites of Knowledge: Knowledge Creation and Application for Sustainable Peace in Africa Moncef Ouannes......................................2 Sociologie D’Une Revolte Armee: Le Cas de la Libye Moncef Ouannes.......................................22 Sociology and Social Work in Nigeria: Characteristics, Collaborations and Differences Ayodele Ogundipe & Patrick Edewor ..............................40 Research Papers Education et Cohésion Sociale en Tunisie Ali Hammami ......................................56 The Representation of Self-Injury and Suicide on Emo Social Networking Groups Carla Zdanow & Bianca Wright ..........................81 Theatre for Development: An Alternative Programme for Reproductive 102 Health Communication in Nigeria Charles Emeka Nwadigwe ................................102 Adolescent Sexuality and Culture: South African Mothers` Perspective Pilot Mudhovozi, Mpho Ramarumo & Tholene Sodi ......................119